Pelatihan Membuat Label Kemasan Produk Pelaku UMKM Kecamatan Bandar Laksamana Kabupaten Bengkalis Menggunakan Canva - Salambue, Roni; Risanto, Joko; Fitriansyah, Aidil; Sukamto, Sukamto; Bahri, Zaiful; Mahdiyah, Evfi; Hidayat, Rahmat; Sujana, Teguh; Sy, Yandiko Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Micro, Small and Medium Enterprises (UMKM) in Bandar Laksamana District, Bengkalis, Riau have been identified by FMIPA students from Riau University who participated in the Belajar Kampus Merdeka (MBKM) Community Service Program (Kukerta) in 2024. There are 66 UMKM in three villages with various businesses such as stalls, fried foods, beauty, culinary, craftsmen. The people of one village seemed apathetic in managing UMKM because they were considered as side businesses only, had no prospects for development and were not interested in participating in online marketing training. From observations, several UMKM products have the potential to be marketed online because they are unique as typical Malay foods. An approach was made to UMKM actors to be assisted in having the skills to design attractive and dynamic packaging labels, assisting online marketing until the market reaches various corners of the country. A good product packaging label will advance the business and introduce the diversity of typical Malay culinary delights to the public. Canva is a simple graphic design application that is easy for beginners to use. Canva provides paid and free services with various easy-to-adopt template features with various completeness such as image cropping, text insertion, color, and so on. The Canva application needs to be introduced to UMKM to attract their product market through unique and attractive banner, poster, and banner designs so that the product display remains fresh, updated according to needs.